Sucessão ecológica do arquipélago Três Ilhas no setor do Alto Rio Paraná - Rodrigues, Elcisley David Almeida (2019)
The objective of this research is to characterize the Vegetative Ecological Succession and the survey of the circumference and height of a group of two fluvial islands located in the upper Paraná River basin, in the city of Querência do Norte / PR. River islands are geoforms established above a level of full margins, endowed with different sizes, age and geomorphological variation. The oscillation of the fluviometric dimensions together with the velocity of the flow, allows the design of different niches and successional phases. In order to reach the main objective, the vertical and horizontal survey of the landscape was used, based on the geosystemic methodology of geoecological profile constructions in order to ascertain the evolution of the vegetation together with the geomorphological dynamics. In this sense, the individuals' circumference and height were collected in accordance with physical attributes such as topography, soil situation and diagnosed habitats. For the data collection procedure, the fixed-installments technique was used. The sample area adopted followed the suggested for the native forest of the region that is the Semideciduous Seasonal Forest of 10,000 m² (1 ha). On the structural survey of the vegetation was used the counting and gauging of the circumference and height of all the individuals located in multiple plots of 10x10 (100 m²). The inclusion criterion employed was the Chest Height Circumference (CAP) ≥ 15 cm and height ≥1.67 cm, in addition to assessing the distribution of the various life forms of the flora. After all the detailing, the construction of a geoecological profile was carried out, which allowed to group the areas in units that had similar topographic characteristics and, finally, the relationship between the local geomorphological evolution and the vegetation development can be verified. The geosystemic methodology also allowed to verify a correspondence of the abiotic elements in the conformation of the structural landscape of the vegetation and in the phases of ecological succession present in the islands.